Endoplasmic Reticulum Stress Induces Macrophages to Produce IL-1β During Mycobacterium bovis Infection via a Positive Feedback Loop Between Mitochondrial Damage and Inflammasome Activation - Liao, Yi; Hussain, Tariq; Liu, Chunfa; Cui, Yongyong; Wang, Jie; Yao, Jiao; Chen, Hehua; Song, Yinjuan; Sabir, Naveed; Hussain, Mazhar; Zhao, Deming; Zhou, Xiangmei (Frontiers in Immunology, 2019)
Mycobacterium bovis, the causative agent of tuberculosis in cattle and humans, infects host macrophages and induces endoplasmic reticulum stress (ERS), mitochondrial damage, and interleukin (IL)-1β production. The relationship between these phenotypes is yet to be elucidated. In this study, we investigated the role of ERS in mitochondrial damage and IL-1β production in macrophages during infection with a virulent M. bovis strain. We found that ERS activates the inflammasome via NOD-like receptor family, pyrin domain-containing 3 (NLRP3)-caspase-8 and that IFN-inducible protein absent in melanoma 2 (AIM2) triggered mitochondrial damage. ERS increased reactive oxygen species (ROS), which promoted translocation of the inflammasome to the mitochondria. NLRP3, but not AIM2, was involved in the ERS-induced cleavage of caspase-8 and Bid, leading to mitochondrial damage, which was required for the production of mature IL-1β. Our data suggest that ERS induces macrophages to produce mature IL-1β during infection with virulent M. bovis through a positive feedback loop between mitochondrial damage and inflammasome activation. To the best of our knowledge, this is the first evidence of the involvement of ERS and mitochondrial damage in inflammasome activation during M. bovis infection.